Service Quality Control Dalam Pengembangan Pembelajaran Bahasa Arab di Excellent Languange - Durrotul Masruroh; Rusli Wan (CV Edujavare Publishing, 2023)
This study aims to examine the Service Qualiti Control in the Development of Arabic Language Learning in the Excellent Languange Region of Zaid bin Tsabit, using qualitative research methods of case study types with observational data collection techniques, interviews, and documentation. To obtain sufficient and clear data in accordance with research problems. Learning Arabic is one of the most important languages to learn and understand in order to understand Islam in depth, by understanding Arabic and being able to communicate using Arabic will make it easier for students to get additional knowledge from someone who conveys their knowledge using Arabic. Arabic has also been included in the international language category. Based on the results of this study, the service quality control used by the Zaid bin Tsabit region towards the development of Arabic language learning towards excellent languange using linguistic elements and skills / skills. In the linguistic element we divide it again into three, namely: mufrodat / vocabulary, understanding ma'na, nahu and tasrif. Likewise, in the element of skill / ability, then we have four stages that we do, namely: maharoh istima', maharoh kalam maharoh qiroah and maharoh kitabah.